Piauí Central Laboratory of Public Health: frequency of mycobacterial species and epidemiological aspects, 2014-2015 - Santos, Mariana Oliveira; de Almeida, Silvia Maria (Revista de Epidemiologia e Controle de Infecção, 2020)
Background and Objectives: Knowledge about species diversity of non-tuberculous mycobacteria (NTM) and the frequency of tuberculosis (TB) is an important issue in ruralurban regions such as Piauí (northeast of Brazil), of low incidence rate of TB , can help to improve diagnosis and prevention strategies. The aim of this study is to examine some epidemiological aspects and the frequency of Mycobacterium tuberculosis (Mtb) and NTM isolated at the central public health reference laboratory, Dr. Costa Alvarenga, Piauí (LACENPI). Methods: Data records of all mycobacterosis and tuberculosis cases from January 2014 to March 2015 were analyzed. Results : Of the 20% (142/706) positive growths, 70% (99) were Mtb and 10% NTM. The remainde was of inadequate clinical samples, not allowing the identification of even the suspected NTM. The most frequent clinical form was pulmonary with TB patients younger than those infected with NTM (p = 0.001), the majority living in Teresina (52%). NTMs identified were M. abscessus (36%), M. avium, M. intracellulare, Mycobacterium sp. (14% each) and M. asiaticum, M. szulgai, M. kansasii 7% (each). Mtb drug resistance (7.8%) and TB co-infection with the human immunodeficiency virus (HIVTB) found to be high (49%, 19/39) . Conclusion: The frequencies of Mtb infection, drug resistance and HIV-TB co-infection are still underestimated and failures in the identification of NTM may decrease the actual frequency of these infections. Therefore, there is a need for improvements in TB control and in the diagnosis of NTMs in Piauí.